Electrical characteristics of multiferroic BiFeO3 electronic system. (2023) - Chauhan, D.; Pradhan, S.K.; Das, S.N.; Bhuyan, S.
Abstract: The structural, dielectric and conductivity properties of bismuth ferrite oxide (BiFeO3 ) electronic system which was synthesized by means of a solid-state reaction route are explained in this literature. For material fabrication, the exact proportion of 99.9 % pure Fe2 O3 and Bi2 O3 was taken and processed. The resulting material is extremely pure and stable in nature. The X-ray Diffraction (XRD) on calcined powder confirms the prepared material's structure as a single-phase rhombohedral crystal system. To understand the electronic behavior in the frequency range of 1 kHz-1 MHz with a temperature range of 35–450 °C, the prepared material was characterized in the form of dielectric and conductivity properties. The synthesized material's normal dielectric behavior has been described. It has a high dielectric constant at high temperatures and a low tangent loss at low temperatures. The tangent loss exhibits lower value at lower temperatures, but as the temperature rises, the plot rises abruptly and reaches a peak around 380 °C. This dielectric loss characteristic is caused by inadequate thermal carriers and oxygen vacancies. The significant grain and grain boundary effect of resistive characteristics of synthesized BFO has been observed at this higher temperature. The frequency-dependent dielectric plots show that the dielectric constant and dielectric loss of the composed material decrease with increasing frequency, regardless of temperature variation. The AC conductivity value decreases with increasing frequency at low temperatures. With the increase in frequency up to 10 kHz, the calculated activation energy of synthesized BFO at a specific temperature region rises. The Fourier transform infrared spectroscopy (FTIR) analysis of the processed material reveals the formation of octahedral FeO6 properties in perovskites mode and many other intriguing results regarding BFO structure. Electronic material may act as a budding contender for designing electronic devices for many useful applications due to all these intriguing characteristics and findings.